Localized PD-1 Blockade in a Mouse Model of Renal Cell Carcinoma - Pham, Ngoc B.; Abraham, Nevil; Velankar, Ketki Y.; Schueller, Nathan R.; Philip, Errol J.; Jaber, Yasmeen; Gawalt, Ellen S.; Fan, Yong; Pal, Sumanta K.; Meng, Wilson S. (Frontiers in Drug Delivery, 2022)
Herein we report the impact of localized delivery of an anti-PD-1 monoclonal antibody (aPD1) on Renca tumors, corresponding T cell responses, and changes in broader immune genes. Renca in BALB/c mice is a syngeneic system that has been used to model human renal cell carcinoma (RCC) for decades. In this study, T cell subsets were examined in tumors and draining lymph nodes of mice treated with localized PD-1 with and without the addition of adenosine deaminase (ADA), an enzyme that catabolizes adenosine (ADO) into inosine. Adenosine (ADO) is a metabolite of ATP and an immune checkpoint molecule in human cancers. aPD1, or aPD1 with ADA (aPD1/ADA) were formulated with the self-assembling peptides Z15_EAK to enhance retention at the tumor inoculation site. We found that both aPD1 and aPD1/ADA skewed the local immune milieu towards an immune stimulatory phenotype by reducing Tregs, increasing CD8 T cell infiltration, and upregulating IFNɣ. Analysis of tumor specimens using bulk RNA seq confirmed the impact of the localized aPD1 treatment and revealed distinct gene expression profiles elicited by the loco-regional treatment. The effects of ADA and Z15_EAK were limited to tumor growth delay and lymph node enlargement. These results support the notion of expanding the use of locoregional PD-1 targeted immunotherapy in solid tumors.